Cysteine Protease from Primrose (Primula vulgaris) - Demir, Yasar; Demir, Nazan; Kaya, Elife; Aydin, Bahar (Asian Journal of Chemistry, 2011)
Proteases are enzymes that perform important functions in organisms and are used for a variety of objectives in vitro. In recent years, proteases have been used for clinical, pharmaceutical (alimentary digestion, antiinflammatory, etc.) and industrial applications (cheese production, meat tenderizing, leather tanning). In this research, a protease has been purified from primrose (Primula vulgaris) and characterized. Primula vulgaris has been used for medicine since ancient times. The plant grows abundantly in certain regions of Turkey. Ammonium sulphate fractionation and a CM Sephadex column were used for purification of the enzyme. The purification enzyme has an optimum pH = 6.0 and its optimum temperature was 60 ºC. The nmax and Km values determined by Lineweaver-Burk graphics were 6.6 mg/L dak and 0.19 mg/mL respectively. The purification degree and the molecular mass of the enzyme (30 kDa) were determined by SDS-PAGE and gel filtration chromatography. It was investigated whether the purified and characterized protease could cause milk to congeal or digest chicken and cow meat. The results show that protease can be used for industrial production.